(untitled) (Experimental biology, 2023)
Mammals are widespread throughout the Pavlodar region. There are data about the species, sex and age composition of the north-eastern region small mammals depends on various distances from the largest factories. The aim was register changes in the micromammalia communities as it get closer to the emission source. The objects collection was carried out with Gero traps – crushers and trap grooves according to Novikov method. Stationary accounting lines and transects was used. 15 species of animals were observed in all areas. The order Rodentia has 11 species, the order Eulipotyphla has 4 species. There is a decrease in the species diversity of small mammals as its approach the factories. The total abundance in technogenic areas is 2 times lower than the control, Microtus gregalis and Sicista subtilis species dominate. This may indicate the high adaptive qualities and ecological flexibility of the dominant species. There are many Sorex Minitus, Sorex araneus, Sorex tundrensis in the control area. Proportion of males increased especially in dominant species (Sicista subtilis, Mictotus gregalis) in the nearest area to the plants. There is the dominance of young animals (64%) in the anthropogenic zone. The air pollution problem is one of the most urgent in the Pavlodar city. The data of the industrial pollutants impact on individual groups of micromammals can serve as a basis for designing anthropogenic facilities.